2004
DOI: 10.1192/pb.28.11.411
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the provision of psychological treatments to older adults in the NHS

Abstract: Aims and MethodA questionnaire was sent to old age psychiatrists to ascertain their experience, views and clinical practice regarding psychological therapies in their services.ResultsThe provision of psychological treatments of all modalities to older people is widely varied in Britain. The main difficulty seems to be a lack of resources, but it would appear that inexperience with psychological therapies applied to older adults is also a factor. Most mental health teams (95%) provide anxiety management therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Psychologists were also the least likely of all groups to be line-managed within CMHTs. The relatively poor access to psychological therapies by older people's teams raises concerns that this gap may be filled by other team members without the necessary training or supervision (Evans, 2004), or simply not provided at all. Furthermore, a recent survey of working-age adult CMHTs in England and Wales found a significant contraction in psychologist membership compared with data from the 1990s (Evans et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Psychologists were also the least likely of all groups to be line-managed within CMHTs. The relatively poor access to psychological therapies by older people's teams raises concerns that this gap may be filled by other team members without the necessary training or supervision (Evans, 2004), or simply not provided at all. Furthermore, a recent survey of working-age adult CMHTs in England and Wales found a significant contraction in psychologist membership compared with data from the 1990s (Evans et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A survey of general practitioners in the UK showed that 93% would consider referring elderly depressed for psychological help but only 44% had actually done so (Collins et al, 1997). Evans (2004) wrote that most old age psychiatrists in the UK would agree that older patients should have access to some kind of psychological services.…”
Section: Introductionmentioning
confidence: 98%
“…Whilst recognising that the delivery of such ambitious goals would take time, the government emphasised the importance of early and systematic progress (Department of Health, 2001). Subsequent reviews made scant mention of the development of mental health services however, and acknowledged they needed attention (Department of Health, 2003, 2004, whilst other influential reports decried the lack of priority given to improving services for older people with mental health problems (Social Services Inspectorate, 2003;Commission for Health Improvements, 2003a, 2003b. This survey provides a detailed picture of the extent to which, some three years after its publication, old age mental health services were delivering the aspirations of the NSFOP (Department of Health, 2001) and gives some indication of the challenges that remain.…”
Section: Introductionmentioning
confidence: 99%